Biofabrication : micro- and nano-fabrication, printing, patterning, and assemblies - Forgács, G.; Sun, Wei (Professor of mechanical engineering) (2013)
Biofabrication is a novel, inherently cross-disciplinary scientific field that focuses on biomanufacturing processes (technologies, materials, devices, models). This is the first book that presents the range of biofabrication technologies (cell printing, patterning, assembling, 3D scaffold fabrication, cell/tissue-on-chips) as a coherent micro-/nano-fabrication toolkit. The book is designed as a practical guide to these key emerging technologies, with real-world examples to help readers gain a working knowledge of how to apply biofbrication techniques.--
In Vitro biofabrication of tissues and organs -- Biomaterials for biofabrication of 3D tissue scaffolds -- Projection printing of three-dimensional tissue scaffolds with tunable Poisson's ratio -- Fabrication of microscale hydrogels for tissue engineering applications -- Polymeric membranes for the biofabrication of tissues and organs -- Laser-assisted bioprinting for tissue engineering -- The modular approach -- Formation of multicellular microtissues and applications in biofabrication -- A digital microfabrication-based system for fabrication of cancerous tissue models -- Breast reconstruction using biofabrication-based tissue engineering strategies -- Fabrication of artificial bacteria for targeted drug delivery -- Biofabricating the bio-device interface using biological materials and mechanisms.
Includes bibliographical references and index.
Keywords: Biomedical engineering; Tissue engineering; Bioengineering; Microtechnology; Nanotechnology; Biomedical engineering; Tissue engineering; 3D-Druck.; Biomaterial; Biomedizinische Technik; Biopolymere; Herstellung; Rapid Prototyping (Fertigung); Werkstoff